Pocketbook on Prophet Hadith to Prevent Bullying Behaviour - Billah, A.A.M; Wantini; Suyatno (Al-Hayat: Journal of Islamic Education, 2024)
The increasing cases of bullying and various forms of violence in Islamic boarding schools have encouraged researchers to develop a Pocketbook containing the Prophet's Hadith which aims to guide students in understanding moral teachings that can prevent violent behavior. This study aims to produce a Pocketbook of the Prophet's Hadith that can be integrated into the Islamic boarding school curriculum to prevent bullying. This media is expected to be a source of inspiration and understanding for students about the importance of avoiding bullying behavior. Research methods are in the form of development research or R&D. The development model used is the 10-step method by Sugiyono. The product's effectiveness is tested by comparing the pre and Post-test values. This study uses data collection techniques through observation, questionnaires, documentation, and interviews. In terms of student response data analysis, evaluation is conducted using the Guttman scale, which includes only two possible answers: "yes" or "no". This research produced the Prophet's Hadith Pocketbook, an effective preventive tool for reducing bullying behavior in Yogyakarta Islamic boarding schools. This media succeeded in increasing students' understanding of anti-bullying values taught in the hadiths of the Prophet. Using this pocketbook decreased bullying behavior among students, showing the effectiveness of this media in supporting character education in the Islamic boarding school environment. This includes limitations in generalizing results because trials are limited to specific populations and have yet to measure their long-term effectiveness. The implication is the importance of developing ethical value-based learning media and its potential adaptation for a broader context.